The Spanish-American war and Philippines insurrection, 1898-1902 an annotated bibliography - Barnes, Mark (Routledge research guides to American military studies, 2011)
An often overshadowed event in American military history, the Spanish-American War began as a humanitarian effort on the part of the US to provide military assistance for the liberation of Cuba from Spanish domination. This book offers a comprehensive and annotated bibliography detailing this globally significant conflict and its aftermath.